Contributions of anthropometric and strength determinants to estimate 2000 m ergometer performance in traditional rowing - Sebastia-Amat, S.; Penichet-Tomas, A.; Jimenez-Olmedo, J. M.; Pueo, B. (Applied Sciences, 2020)
Contributions of Anthropometric and Strength Determinants to Estimate 2000 m The purpose of this study was to analyze the contribution of anthropometric and strength determinants of 2000 m ergometer performance in traditional rowing. Nineteen rowers competing at national level participated in this study. Anthropometric characteristics, vertical jumps and bench pull tests were assessed to determine conditional factors, whereas the 2000 m test was used to set rowing performance. Pearson correlation coefficient, linear stepwise and allometric regression analyses were used to predict rowing performance (R2 > 50%). Height, body mass and body muscle correlated with rowing performance in male and female rowers. Similarly, power output for squat jump and countermovement jump power correlated with performance. Finally, mean propulsive velocity, mean power and maximum power in bench pull also correlated with the test. Stepwise multiple regression analysis identified body mass (R2 = 0.69, p < 0.001) and mean propulsive velocity in bench pull (R2 = 0.76, p < 0.001) for male rowers and body muscle (R2 = 0.89, p = 0.002) and maximum power in bench pull (R2 = 0.62, p = 0.036) for female rowers as the best predictors of rowing performance. These results determine the relevance of anthropometric characteristics and, in contrast to Olympic rowing, support the greatest importance of upper body power in traditional rowing training.